Indonesian Student Perceptions of Learning Kanji - Renaldy, R; Setiana, S M (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to describe the perception of learning Kanji in the Moji Goi course. This study uses a descriptive evaluative method with an online survey approach via Google Forms. Respondents in this study were 54 grade 1 students of the Japanese Language Department at the Indonesian Computer University for the 2022/2023 Academic Year. The results showed that students stated that learning kanji is important, more than students stated that the addition of learning media with e-learning with structured material was the right learning method. The problems that occur when learning kanji are that it is difficult to memorize kanji because it has many meanings, it is difficult to write kanji because there are many streaks, and boredom arises because the learning process is monotonous. The solution to this problem is to improve the ability of lecturers to carry out Kanji learning using a variety of teaching methods. Us of the e-learning method with structured material by lecturers is considered to be the right solution because learning materials ca about be accessed anywhere For In addition, lecturers always motivate students to be enthusiastic about attending lectures. For students' Japanese language skills to continue to improve, it is necessary to motivate students and the ability of lecturers to carry out quality Kanji learning using various teaching techniques.